ANALISIS PEMASARAN DAN SIKAP KOSUMEN TERHADAP PEMBELIAN IKAN PATIN SALAI UMKM BINAAN INKUBATOR AGRIBISNIS UR - Samosir, Juliati; Rifai, Ahmad; Restuhadi, Fajar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The fisheries sector(which is madeup of capturefisheries and aquaculture) is one of the most important household economics in Kabupaten Kampar, both from economic and social standpoints. The fisheries, particularly catfish, have also significant role in supplying community’s consumption for animal protein in the area, increasing fishermen revenue, and providing employment opportunities. Given the nature of the fishery products as a perishable product, the most common method to preserve the fish is by smoking the fish. The smoked fisheries industry further supports almost 12 % of households (directly and indirectly), and contributes to the livelihood, employment, and household food security, especially forcommunities live along the Kampar’s Delta. Currently, several fisheries small-holder’s enterprises were assisted by The Agribusiness Incubator, University of Riau, in terms of processing, packaging, and marketing techniques. This research was aimed to study marketing and behavioural analysis of smoked catfish produced by the enterprises. Most of the respondents are at productive age (15-54 years), with a high school education or equivalent level, and the average amount of revenue per month ranged between Rp. 2,600,000 to Rp. 5,000,000.  The respondent’s family members are in the category of small (2-3 people). The respondents mostly purchase the smoked catfish directly to the Wholesale/Dealer/Collector. The respondent’s purchasing decision is mostly affected by the following product attributes: packaging, point of sale location, and service offered by the seller. Plotting the product’s attributes in the Cartessian diagram shows that the first quadrant is filled by the following attributes: product’s aroma, brand, price, and smoked fish color. The second quadrant is described by hygienic properties, weight per pack, taste, and saltiness property. Meanwhile, for the third quadrant is positioned by the products’s nutrition information and labeling; as well as for the fourth quadrant is the location of sales, service sales, and forms of packaging. Based on the analysis of Fishbein’s Multiatributes, the respondent’s attitude is considered as fairly-good on the multiattributes categorical approach. Keywords: Smoked Catfish, Consumer’s Behaviour, Fishbein’s Multiatribute, Cartessian Coordinate Analysis